2013
DOI: 10.1016/j.jpain.2013.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Endomorphin 2 Antinociception and the Mechanisms That Produce It Are Both Sex- and Stage of Estrus Cycle–Dependent in Rats

Abstract: Endomorphin 2 (EM2) is the predominant endogenous mu-opioid receptor (MOR) ligand in the spinal cord. Given its endogenous presence, antinociceptive responsiveness to the intrathecal application of EM2 most likely reflects its ability to modulate nociception when released in situ. In order to explore the physiological pliability of sex-dependent differences in spinal MOR-mediated antinociception, we investigated the antinociception produced by intrathecal EM2 in male, proestrus female, and diestrus female rats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
35
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(36 citation statements)
references
References 66 publications
(82 reference statements)
1
35
0
Order By: Relevance
“…Our laboratory recently demonstrated that spinal EM2 antinociception is not only greater in male rats than diestrous female rats, but also greater in proestrous than diestrous females [45]. We therefore hypothesized that regulation of spinal EM2 release is also sex and cycle dependent.…”
Section: Introductionmentioning
confidence: 99%
“…Our laboratory recently demonstrated that spinal EM2 antinociception is not only greater in male rats than diestrous female rats, but also greater in proestrous than diestrous females [45]. We therefore hypothesized that regulation of spinal EM2 release is also sex and cycle dependent.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that morphine activates serotoninergic dorsal raphe nucleus neurons. Microdialysis of this opioid into rat forebrain increases serotonin release in the nucleus accumbens, frontal cortex, amygdaloid nucleus, dorsal striatum, thalamus, hypothalamus and hippocampus [12].In 1989, investigations performed on female rats allowed for concluding that endogenous androgens and oestrogens could play a significant role in morphine efficacy in the visceral pain model [13].It has been proven in females that antinociceptive activity of endomorphin 2 located in the spinal cord ranged between analgesically active and inactive states [14]. When circulating oestrogens are low during dioestrus, female rats demonstrate increased sensitivity to pain.…”
mentioning
confidence: 99%
“…The antinociception properties of spinal endomorphin 2 could be modulated by changes in concentration of sex hormone. It depends on both the rat's sex and the stage of the oestrus cycle [14].Noteworthy is the occurrence of sexual dimorphisms in neuron counts in the periaqueductal grey-rostral ventromedial medullary pathway (PAG-RVD) [15] and for the occurrence of opioid receptor expressions within the periaqueductal grey (PAG) [16]. Opioid receptor expression is probably lower in…”
mentioning
confidence: 99%
See 2 more Smart Citations